La parémiologie musicale de Kastner : une introduction à l’oeuvre (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
This study is an introduction to Kastner’s Musical Paremiology of the French Language (1866). It is a singular and remarkable work which, first of all, deserves its place in historical phraseology, in that the author attempts to situate the expressions in the evolution of the language and to reconstruct the process of their creation. Secondly, it is a pioneer among dictionaries of specialised paremiology. The proverbs and expressions classified by Kastner are drawn from different sectors of music and reflect the multiplicity of his interests: instruments, voices, rhythm and even birdsong. For its richness and erudition, this book should become a reference base for paremiologists, as it is for musicologists, with regard to its terminological data. Following a presentation of the dictionary, my study focuses on the proverbs of a poetic text in the appendix: Symphony-cantata. Saint-Julien of the minstrels.
Keywords: musical paremiology, Kastner, phraseology, specialised proverb